Design and Realization of a Refuse Sorting System for Educational Perspective - A. Allal; A. Chemsa; A. Khechekhouche; S. Saadallah; A. Bouhelal; D. Korti; A. H. A. Lammari (Indonesian Journal of Educational Research and Technology, 2024)
Our project focused on developing a waste sorting machine for metal, plastic, and glass for educational purposes. We divided it into several parts, including waste types, sorting methods, and recycling processes. All processes were done highlighting the use of the Arduino Uno controller. Additionally, we outlined the tools required for an automated sorting system and go beyond simulations by creating a prototype. Our goal is to establish a waste sorting machine that promotes recycling and environmental protection, providing both financial returns and sustainability by diverting waste from burial or incineration, thus mitigating pollution.